Responsibility for Fulfilling the Rights of Women Prisoners - Nur Paikah (Journal of Indonesian Scholars for Social Research, 2023)
The purpose of this study is to review the implementation of government responsibility for fulfilling the rights of women prisoners at the Class IIA Watampone Correctional Institution. The type of research used is qualitative, using an empirical juridical approach, namely analyzing the articles in the applicable laws and regulations related to legal facts in the field. The results showed that the government's responsibility for the fulfillment of the rights of women prisoners at the Class IIA Watampone Penitentiary has not been fully effective due to several indicators of weak performance achievement, namely facilities and infrastructure that are not yet feasible due to budgets that are not yet human rights-based so that room facilities are still overcapacity. Health clinics and medical personnel are only permanently recruited at the Class IIA Watampone Penitentiary. As a result, the fulfillment of the rights of women prisoners still needs to be improved and optimal as mandated by Law Number 39 of 1999 concerning Human Rights and Law Number 12 of 1995 concerning Correctional Institutions (LAPAS).